Effect of Grape Temperature and Yeast Strain on Sauvignon blanc Wine Aroma Composition and Quality - Marais, J. (South African Journal of Enology and Viticulture, 2017)
The study focused on the production of Sauvignon blanc wines from grapes grown in sub-optimal climatic conditions. Grape temperatures of l0°C and 25°C at harvest, and fermentation with different Saccharomyces cerevisiae yeast strains, i.e. VIN 13, VIN 7, NT 116 and NT 7, were investigated over three seasons (1998, 1999 and 2000). The highest quality wines were produced from the cooler 10°C grapes. Choice of yeast strain was complicated by effects of factors such as grape temperature, grape maturity and season. In general, the highest ester concentrations and lowest higher alcohol concentrations were produced by NT 116, and the highest wine quality by NT 7. Strain VIN 7 yielded the lowest ester levels, which in some cases were preferred, since the masking effect of esters was diminished with the result that Sauvignon blanc wines with more pronounced cultivar-typical green notes and consequently higher quality could be produced. Therefore when Sauvignon blanc grapes, known to produce neutral wines, are used, factors such as low temperature at harvest and yeast strains suitable for these conditions should be considered.